Ethnocultural Reflexes of a Language Border Zone in Regional Phytonymic Lexicon of Belgorod Region (On Materials of Dialectological Researches for Department of Russian Language and Russian Literature of NIU "BELGU") - Kosharnaya, Svetlana A.; Plotnikova, Larisa I.; Ozerova, Elena G.; Nagornyy, Igor A.; Novikova, Tatiana F. (Journal of History Culture and Art Research, 2018)
The results of long-term field dialectological studies fulfilled of the Department of Philology of Belgorod State National Research University are presented in the article. During these studies the departmental catalog of the folk dialects of Belgorod has been collected. Regional dialect and Belgorod region dialects pose a less understood layer in the Russian dialectic corpus. The term "regional dialect" is interpreted as a specific language formation functioning within the boundaries of the region and absorbing local speech features. Belgorod dialects and regional dialects, being a language type of a border zone region, despite its relative "marginality" in the Russian dialectal system, are a significant object of dialectological description and a source for domestic historical linguistics. Herein they are associated with the dialects of the territories of late settlement. Therefore the crucial tasks are to make linguistic and linguocultural analysis of the Belgorod regional and dialectal vocabulary, to identify and describe the basic lexico-semantic groups, to view the systemic relations within lexical groups, correlation between dialectal and national language vocabulary, to explore borrowings and their sources. This will allow speaking not only about different types of variability and synonymous relations between dialectal and national language units, but also about the formation and evolution of Russian dialects and the language as a whole. Often, dialectal phenomena are caused by the influence "from outside". This is more peculiar to outlying dialects, which are affected by foreign-language neighborhood. At the same time, as a whole, dialects of Belgorod region are Russian in their base morpheme and by their origin and often preserve the language antiquity. Thus, at the Belgorod territory, there is a clash of different ethno-linguistic streams and traditions. In this context, plant world nominations are of special interest in the system of Belgorod dialectal and regional vocabulary.